“Características de los antibacterianos de mayor prescripción en el Centro de Salud Casa Grande, Julio 2015 – Junio 2016 - Santillán Huallán, Jessica (2017)
The present report aims to determine the characteristics of the most prescribed antibacterials in the Casa Grande Health Center during the period from July 2015 to June 2016. The information was obtained from the database of reports of Integrated Consumption Report ICI - SISMED, of the mentioned period, the results obtained from the months of July 2015 and June 2016 in terms of the monthly average evolution of the antibacterials was 4687.6, the monthly percentage of antibacterial time and dependent dose were determined being these of 89 , 3% and 10.7% respectively; the average percentage of the monthly antibacterial prescription with bactericidal and bacteriostatic effect was 84.93% and 15.07% respectively, the antibacterial with the highest bactericidal effect was amoxycillin with 35.7%, the antibacterial with the highest bacteriostatic effect was erythromycin with 61.91%. It was concluded that the antibacterials with the highest prescription were those with the following pharmacodynamic characteristics: bactericidal effect and time dependent